Impact of Tourism on Economic Growth of Nepal: Is Tourism-Led Growth Hypothesis Valid for Nepal? (The Gaze: Journal of Tourism and Hospitality, 2022)
A voluminous study is available on tourism-growth nexus as tourism industry received considerable attention as a potential source of economic growth. This paper empirically examines the impact of tourism on economic growth of Nepal by using time series data of 1976-2020 and applying autoregressive distributed lag (ARDL) approach. Real GDP was used as proxy measure of economic growth, which was the outcome variable whereas the variable of interest was tourism receipts. Foreign aid, total volume of trade and ratio of government consumption expenditure to GDP were taken as control variables. The result of ARDL model shows that tourism has no significant impact on economic growth of Nepal in both short-run and long-run. However, total volume of trade has positive and significant effect on economic growth in short-run whereas foreign aid, total volume of trade and ratio of government consumption expenditure to GDP have positive and significant effect on economic growth in the long-run. In such context of tourism and growth relationship, tourism-led growth hypothesis is rejected for Nepal.